Carcass and meat quality of Nellore cattle (Bos taurus indicus) belonging to the breeding programs - Malheiros, Jessica Moraes [UNESP]; Enriquez-Valencia, Cruz Elena; Silva, Josineudson Augusto II de Vasconcelos [UNESP]; Curi, Rogério Abdallah [UNESP]; de Oliveira, Henrique Nunes [UNESP]; de Albuquerque, Lúcia Galvão [UNESP]; Chardulo, Luis Artur Loyola [UNESP] (Elsevier, 2020)
The objective of this study was to estimate and describe phenotypic traits for carcass and meat quality in Nellore cattle belonging to the breeding programs. Data from 718 Nellore animals participated in the Delta Gen, CRV Paint and Nelore Qualitas breeding programs were used. Meat quality traits were measured and the data were analyzed. The following means and standard deviations of the meat quality traits were obtained: shear force (SF = 5.7 ± 1.3 kg), myofibril fragmentation index (MFI = 32.0 ± 15.3), cooking loss (CL = 27.7 ± 3.1%), intramuscular lipid content (ILC = 0.9 ± 0.5%), backfat thickness (BFT = 4.2 ± 1.4 mm), marbling score (MS = 2.6 ± 0.36), rib eye area (REA = 72.8 ± 7.35 cm2) and instrumental color (lightness (L* = 27.9 ± 2.7), redness (a* = 12.4 ± 1.86), yellowness (b* = 5.5 ± 1.0)). Significant phenotypic correlations were observed between BFT and MS (0.2314), and between MS and ILC (0.1308). A negative and significant correlation was found between SF and MFI (-0.5525); however, the correlation with MFI was low in animals with SF values ​​higher than 6 kg. In principal component analysis (PCA), the first four eigenvalues of the matrix of direct additive genetic variance explained 61.26% of the total additive genetic variance in the meat quality traits. The most important meat quality traits in PC1 were a*, b* and CL. PC2 was characterized by MFI and color (a* and b*), PC3 by MS, BFT and L* and PC4 by ILC, L* and b*. Furthermore, BFT was positively associated with MS, SF and CL, and SF was negatively associated with MFI. The present study suggests that muscle growth and backfat thickness were satisfactory; however, intramuscular fat deposition and meat tenderness still require more attention from the breeding programs.
Keywords: beef cattle; rib eye area; shear force; Zebu genotype